The Impact of Population Density and Economic Growth on Environmental Quality: Study in Indonesia - Wafiq, Abdulloh Nashiruddin; Suryanto, Suryanto (Universitas Muhammadiyah Yogyakarta, 2021)
Sustainable economic growth is followed by an improvement in environmental quality. The purpose of this study is to identify the correlation between economic growth and population density on the environmental quality index (EQI) in Indonesia. In addition, it also aims to determine the impact of economic growth and population density on the environmental quality Index. This study uses a quantitative method with secondary data from 33 provinces in Indonesia from 2010 to 2016. Data were analyzed using Pearson correlation and panel data regression. The result showed that the correlation between economic growth and population density on the quality of the environment was moderate. It has a significant negative impact on environmental quality.